The effect of gentle touch on cardiorespiratory indices and pain behaviors related to venipuncture and blood sampling in preterm infants under intensive care - Pariya Bahrami; Elaheh Sheikhan; Zohre Shams Soulari; Mehri Golchin (Wolters Kluwer Medknow Publications, 2023)
Background: Infants undergo extremely painful procedures in a Neonatal Intensive Care Unit (NICU), which if left uncontrolled may cause complications. Therefore, this study was conducted to investigate gentle touch effect on cardiorespiratory indices and pain behaviors related to venipuncture and blood sampling in preterm infants. Materials and Methods: A quasi-experimental study was undertaken in gentle touch and control groups in three stages. The population included premature infants in NICU of Al-Zahra Hospital, Isfahan, Iran. Using convenience sampling, 52 infants were randomly selected and assigned to two groups (n = 26). Gentle touch technique and measurement of cardiorespiratory indices were performed 5 minutes before, during, and 5 minutes after procedure, and routine care was provided for control group. Neonatal pain and cardiorespiratory indices were assessed using the Neonatal Infant Pain Scale (NIPS) and an intensive care monitor. Data was analyzed using repeated measures ANOVA, independent t-test, and Chi-square test in SPSS software. Results: The independent t-test revealed a significant difference between mean pain score of the infants in two groups during the procedures (t50 = -3.32, p = 0.002), but no significant different was between groups before and after the procedure (p > 0.05). However, the cardiorespiratory indices were not significantly different before, during, and after the procedure (p > 0.05). Conclusions: The results suggest that gentle touch reduced the infants' pain during venipuncture and blood sampling. Thus, it is recommended this method be applied to mitigate pain in premature infants.